2021
DOI: 10.1016/j.psj.2021.101078
|View full text |Cite|
|
Sign up to set email alerts
|

Direct surface wetting sprinkler system to reduce the use of evaporative cooling pads in meat chicken production: indoor thermal environment, water usage, litter moisture content, live market weights, and mortalities

Abstract: An overhead sprinkler system that directly applies water onto meat chickens in tunnel ventilated houses was evaluated and compared with a conventional evaporative cooling pad system at 2 commercial farms in south-eastern Queensland, Australia. The sprinkler system was used to reduce the use of evaporative cooling pads as the primary cooling system but not replace evaporative cooling pads altogether. The sprinkler system used low water pressure and comprised evenly spaced sprinklers and a programmable controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(7 reference statements)
2
2
2
Order By: Relevance
“…This is in agreement with findings from [ 31 ] who reported no significant effect by sprinklers on litter moisture content. However, it does not agree with research by [ 50 ] who found moisture content differed with a two-way interaction between growout × sprinklers ( p = 0.002), with slightly drier litter in the sprinkler house. A weaker relationship was also found by [ 50 ] when sprinklers were considered as a main effect ( p = 0.046), where litter moisture was slightly lower in the sprinkler houses.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…This is in agreement with findings from [ 31 ] who reported no significant effect by sprinklers on litter moisture content. However, it does not agree with research by [ 50 ] who found moisture content differed with a two-way interaction between growout × sprinklers ( p = 0.002), with slightly drier litter in the sprinkler house. A weaker relationship was also found by [ 50 ] when sprinklers were considered as a main effect ( p = 0.046), where litter moisture was slightly lower in the sprinkler houses.…”
Section: Resultscontrasting
confidence: 99%
“…However, it does not agree with research by [ 50 ] who found moisture content differed with a two-way interaction between growout × sprinklers ( p = 0.002), with slightly drier litter in the sprinkler house. A weaker relationship was also found by [ 50 ] when sprinklers were considered as a main effect ( p = 0.046), where litter moisture was slightly lower in the sprinkler houses. In the current study, we did see slightly drier litter in the sprinkler/cool cell combination house.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Aside from drinking water, the major consumptive use of water at the farm was for cooling. Innovations or management changes in cooling, such as combined sprinkler and evaporative cooling pads (Dunlop and McAuley 2021) may offer reductions in on-farm water consumption.…”
Section: Main Impact Sources In the Supply Chainmentioning
confidence: 99%